PENGARUH PELATIHAN SOFT SKILL, PELATIHAN HARD SKILL, DAN TINGKAT PENDIDIKAN TERHADAP KUALITAS SUMBER DAYA MANUSIA DI UMKM TOMIMASE UIN SUMATERA UTARA - Budi Februari; Zuhrani Gumas Damanik; Siti Chairinnisa Hardi; Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the influence of soft skills training, hard skills training, and level of education on the quality of human resources at UINSU Tomimase UMKM. This research uses quantitative analysis methods. The research results show that partially, hard skills training has an effect on the quality of human resources in TOMIMASE UINSU UMKM, while soft skills training and education level have no effect. Simultaneously, soft skills training, hard skills training, and education level have an influence of 65.6% on the quality of human resources at TOMIMASE UINSU UMKM.